The Adequacy of Financial Reports and The Need For Additional Reporting In The Public Sector - The Perspective of Accountants in Croatia - Martina DRAGIJA KOSTIC; Ivana PAJKOVIC; Josip CICAK (Communications of International Proceedings, 2022)
Financial reporting of public sector entities has been in in a constant process of reform due to the growing and changing requirements of information users. Therefore, this paper investigates the perception of accountants about adequacy of financial reporting system of public sector entities in Croatia and the need for additional forms of reporting for different groups of information users. We have developed two goals of the paper as follows: to analyse the legislative context of financial reporting and the possibility of conducting reforms and applying international standards; to research the perception of accountants on the adequacy of financial reports based on the modified accrual base for different categories of information users and the need for additional reports. The results of the research, which were obtained through empirical research conducted in 2022 in Croatia, showed that accountants believe that the current financial reporting system is not entirely appropriate. However, they did not express an overly positive attitude towards reforms and changes in the financial reporting of public sector entities, as well as the need for additional forms of reporting.
Keywords: public sector accounting; financial reporting; accountants; Croatia